Lingua-Didactic Aspects of Teaching Mining Vocabulary to Mining Engineers - Marinova Elena; Rabkina Nadezda; Ryabova Marina; Valko Olga (E3S Web of Conferences, 2018)
The current paper features the problem of teaching foreignlanguage mining vocabulary to would-be translators / interpreters and mining students. The one-industry city environment poses a challenge in front of those higher education institutions that offer a master degree in translation: as long as the best jobs in the region are offered by coal-mining enterprises, developing language and translation skills is not enough. A professional translator in a coal-mining region has to be familiar with mining vocabulary, which, like in any other high-tech production sphere, seems either too abstract or too specific for an outsider. Bachelors in coal mining, on the other hand, demonstrate a lack of communication skills if they wish to get a master degree in translation. The article states Content and Language Integrated Learning method (CLIL) as a possible solution for the problem. The method allows the instructor to employ various authentic media sources within the mining works to build up topic cases for communication skills development at the initial stage as well as to extract terminology to compile thematic glossaries at a later stage of translation skills acquisition. The paper includes some examples of CLIL application in teaching translation for coal-mining industry purposes.